2016
DOI: 10.1007/s10802-016-0224-y
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Prenatal and Early Childhood Fish and Processed Food Intake, Conduct Problems, and Co-Occurring Difficulties

Abstract: Little is known about early life diet as a risk factor for early-onset persistent conduct problems (EOP CP). To investigate this, we used data from the Avon Longitudinal Study of Parents and Children, a UK-based prospective epidemiological birth cohort. 5,727 mother-child pairs (49.9% boys) monitored since pregnancy (delivery date between 1 April, 1991 and 31 December, 1992) reported intake of fish and processed foods at 32 weeks gestation and, for the child, at 3 years; EOP (n=666) and Low conduct problem (Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…These results are consistent with the finding from a recent meta-analysis of studies on maternal diet quality and child development in Western industrialized countries published up to November 2016 (23). The results are also in agreement with more recent studies reporting associations between prenatal diet quality and less child hyperactivity (66, 67), fewer emotional problems (66), and higher verbal and full-scale intelligence quotient (68).…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with the finding from a recent meta-analysis of studies on maternal diet quality and child development in Western industrialized countries published up to November 2016 (23). The results are also in agreement with more recent studies reporting associations between prenatal diet quality and less child hyperactivity (66, 67), fewer emotional problems (66), and higher verbal and full-scale intelligence quotient (68).…”
Section: Discussionsupporting
confidence: 92%
“…Previous observational studies on risk of SDQ among children also reported smaller effect size. For example, a previous study of the associations between early childhood fish and processed food consumption and conduct problems assessed by SDQ reported the effect sizes of η 2 = 0.001, which can be interpret that effect of fish and processed food explained 0.1% of child SDQ ( 36 ). Thus, although the impact of late or irregular parental time retuning home is small, it cannot be ignored as other important risk factors on child behavior problems showed similar effect size.…”
Section: Discussionmentioning
confidence: 83%
“…This is in line with the small association estimates found in a previous review and meta-analysis investigating maternal diet quality and child neurodevelopmental outcomes. More recently, Mesirow and colleagues [ 70 ] studied aspects of maternal diet quality in relation to child behavioural issues in children with either low conduct problems or early-onset persistent conduct problems. They found that, specifically for children presenting with early-onset conduct problems, mothers had a poorer diet quality (lower fish intake, higher processed food consumption) compared to mothers with children having low conduct problems.…”
Section: Discussionmentioning
confidence: 99%